Cascade and direct processes in multiple Auger decay of core-excited states of N2. Issue 14 (January 2020) - Odagiri, T; Taniguchi, T; Kaneyasu, T; Tanaka, H; Adachi, J; Lablanquie, P; Hikosaka, Y
Synopsis: We report here a detailed experimental study on multiple Auger decay after core excitation into the π * valence and Rydberg orbitals in N2 by an electron-electron coincidence technique.